Animal ethical mourning: types of loss and grief in relation to non-human animals - Pihkala, Panu; Aaltola, Elisa (Frontiers in Veterinary Science, 2025)
People can feel various kinds of loss and grief in relation to non-human animals. This has been increasingly studied in relation to pets and companion animals. Recent explorations of ecological grief include wildlife loss, and emerging studies observe grief among veterinarian professionals, zoo personnel, and animal researchers. People can mourn many kinds of animals, including farmed animals, but there is a need for more research on the topic. In this interdisciplinary article, we draw attention to various forms of what we call animal ethical mourning: grief experienced as a consequence of moral commitment to animals. We chart many new aspects by applying Pihkala’s recent framework of Ecological Sorrow (2024) into three case examples: companion animal grief (including pets), wildlife grief, and farmed animal grief. We find many kinds of loss and grief in relation to the case examples, and we propose two new terms for socially contradicted forms of animal ethical mourning: “contested grief” and “contrapuntal grief.” The results are useful for anyone who either experiences animal ethical mourning or wishes to provide more understanding for it in societies. The findings can also inform practices in workplaces which include animals.